Analisis Jual Beli Followers Instagram Menurut Perspektif Ekonomi Syariah - Sulaeman Sulaeman; Anggi Setya Prayoga (STEBI Global Mulia Cikarang, 2022)
Buying and selling online is now widely known by the public. Many phenomena occur on one of the social media in the form of Instagram, which is the most popular place for online sales and for popularizing accounts. In buying and selling online on Instagram, many sellers (traders) use the services of buying and selling followers on Instagram so that their online shop is known by many people and is more trusted. Apart from that, there are not a few phenomena that misuse buying and selling followers as a means of online fraud. The purpose of this study is to find out the practice of buying and selling Instagram followers in the Dark Store, and to find out the practice of buying and selling Instagram followers in the Dark Store according to a Sharia Economic perspective. Social media is an important part of human life in this digital era. The function of social media in doing business is used as a media for product promotion. One of the buying and selling that uses technology as a medium is buying and selling online. Buying and selling online is mostly done by some people because of the convenience in making transactions, namely not having to meet directly between the seller and the buyer. This research approach uses qualitative research methods. Qualitative research is research that produces analytical procedures. The purpose of this qualitative research is to understand the condition of a context by directing it to a detailed and in-depth description of the portrait of the condition in a natural context (natural setting), about what actually happened according to what it is in the field of study. The mechanism used in the practice of buying and selling followers is carried out like buying and selling online. If viewed from buying and selling in general based on the Fatwa of the National Sharia Council-Indonesian Ulema Council Number 110/DSN-MUI/IX/2017 through the suitability table there is sharia incompatibility in buying and selling followers. Buying and selling followers is included in illegal buying and selling because the object being traded is not clear in form or in terms of the ownership status of the object, it does not completely belong to the seller or there is no permission from the owner. So the conditions and pillars of the sale and purchase are not fulfilled. Then secondly, from the point of view of the benefits in buying and selling followers, it tends to bring a lot of harm and is prone to fraud and this transaction contains an element of taking advantage of narrowness which contains deception so that one party loses out. This can be seen from the object being traded is not in accordance with the agreement at the beginning so that there is a loss from the buyer regarding the reduced number of followers he bought quickly without the buyer knowing at the beginning of time and there is no guarantee or guarantee from the seller for active followers. This buying and selling still has its benefits but is fictitious in nature, it can even lead to fraud which can harm the public and consumers.